Evaluating pre-service science teachers’ concept mastery in the topic of biodiversity during distance learning under circumstance of Covid-19 pandemic - Aida Fikriyah; Bayu Sandika; Etistika Yuni Wijaya (Jurnal Inovasi Pendidikan IPA, 2020)
Students as pre-service science teachers have to reach concept mastery during learning process, since it includes in a teachers’ pedagogical competence that has to be attained well. Although this current circumstance is under covid-19 pandemic, however distance learning should provide an effective situation that can gauge students’ concept mastery. This study aims at evaluating pre-service science teachers’ concept mastery in the topic of biodiversity during distance learning under circumstance of covid-19 pandemic. The research included in a descriptive quantitative study. The distance learning was conducted in the lecture of bioconservation during odd semester, on September 2020 toward 50 students in the year academic of 2017. Data were collected using an online test consisting of 10 multiple choice questions. Findings indicates that the pre-service science teachers’ concept mastery reached a score of 53.0 in which was categorized as moderate criteria. Therefore, it can be concluded that the concept mastery has to be enhanced continually in every learning process in order pre-service science teachers are able to comprehend science concepts and enhance this mastery respectively.